The chemistry of wet deposition flux in Istanbul, Turkey - (:unkn) unknown (My University, 2011)
This study presents the relationships between the wet deposition fluxes of chemical species, their concentrations and the rain intensity in the precipitation events which took place on a) November 10th, 2007 b) September 08th, 2007, 29 sequential rain samples were collected in those three precipitation events in Istanbul-Turkey using a sequential precipitation sampler. Temporal variation of chemical species were investigated during the events and found that the variability of ion concentrations were similar to each other for almost all of the precipitation events. With progressing time during the rain events, concentrations of pollutants in the atmosphere decreased, thus leading to less and less measured concentration of all chemical species in the rainwater. It is believed that the dominant factor in this reduction was washout and rainout scavenging acting together in the beginning of the precipitation event. There was strong correlation between rain intensity and wet deposition flux for all ions except K+ in the sequential samples collected on November 10th, 2007. Strongest relation between the concentrations of chemical species and wet deposition fluxes was obtained for September 08th, 2007. © SGEM2011 All Rights Reserved by the International Multidisciplinary Scientific GeoConference SGEM.
Keywords: Rain intensity; Sequential rain sampling; Washout